Homerische Träume und Herodoteische Traumdeutung - Ritoók, Zsigmond (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
It is not too probable that the interpretation of dreams to be read with Herodotus (VII, 6β) is of Persian origin. Nevertheless, the dreams told by Homer correspond to the Herodotean interpretation: The dreamer dreams by night of things which he concerns himself with by day.